Survey on Hardware Trojan Detection Techniques - Mrs G K Sandhia (International Journal of Psychosocial Rehabilitation, 2020)
Hardware Trojan (HT) is a malevolent alteration of the circuitry of an IC. These are harmful to the security of the systems which are built on such malicious integrated circuits. Owing to the trend of globalization in the Integrated Circuit Industry, companies often outsource the design and fabrication of ICs to third-party vendors. The consequence of this trend is the potential existence of unlawful stealthily inserted Hardware Trojans which has resulted in a great security concern, and demands identification and detection of vulnerable HTs possible in different components of machine such as memory/cache system. The several types of intentional modification of the circuits result in the outcome of adversarial effects on the computer architecture. In this paper we discuss the various problems that are faced when detecting such Trojans and the solutions that have been created in order to counter such obstacles as well as their convenience. The methods that have been surveyed are applied at different stages of production of the ICs. The techniques used together with their limitations have also been surveyed.